2009
DOI: 10.2139/ssrn.1490925
|View full text |Cite
|
Sign up to set email alerts
|

Securitization and Bank Performance

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. tend to be more profitable institutions, with higher credit risk exposure. Despite a more diversified funding structure, they face higher funding costs. We also find that securitizing banks tend to hold larger and less diversified loan portfolios, have less liquidity, and hold less capital. However, our analysis does not provide evidence to suggest that securitization had an impact upon bank p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As well as auditor premium studies, a common focus of A&F research is the evaluation of treatment effects. For instance, the performance of banks employing a policy of securitization (the ‘treated’ group) compared to those (the ‘control’ or ‘untreated’ group, or ‘counterfactuals’) who do not (Sarkisyan et al, 2009). In assessing treatment effects, it is usual to compare the means of the outcome variable in the treatment and control groups.…”
Section: The Selection Bias Issuementioning
confidence: 99%
See 1 more Smart Citation
“…As well as auditor premium studies, a common focus of A&F research is the evaluation of treatment effects. For instance, the performance of banks employing a policy of securitization (the ‘treated’ group) compared to those (the ‘control’ or ‘untreated’ group, or ‘counterfactuals’) who do not (Sarkisyan et al, 2009). In assessing treatment effects, it is usual to compare the means of the outcome variable in the treatment and control groups.…”
Section: The Selection Bias Issuementioning
confidence: 99%
“…This may explain the increasing use of PS matching across a wide range of A&F topics. For example, recent studies have employed the technique to examine the impact of social responsibility on firm value (Rossi, 2009), takeovers on corporate performance (Jurajda and Stancik, 2009), analysts’ recommendations on stock performance (Ertimur et al, 2009), cash flows disclosures on earnings (Orpurt and Zang, 2009), securitization on bank performance (Sarkisyan et al, 2009) and the precision of investors’ information (Cuijpers and Peek, 2010).…”
Section: The Selection Bias Issuementioning
confidence: 99%
“…(For a summary of some of these studies see Panetta and Pozzolo [2010], who study credit risk transfer in over 100 countries.) For example, a recent working paper, using propensity scoring techniques to try to determine a counterfactual (had banks not chosen to securitize) fi nds that after controlling for whether banks choose to securitize, there is no statistically signifi cant impact of securitiza-tion on banks' funding costs, credit exposure, or profi tability (Sarkisyan, et al 2010). While the authors frame the work in terms of a counterfactual, it addresses a far narrower question: How would banks have performed had they not used securitization (but implicitly assuming that securitization exists and is used by other institutions)?…”
Section: Identifying Counterfactual Alternativesmentioning
confidence: 99%
“…Odhiambo (2015) found that the relationship between property finance and the financial performance of banks listed on the Nairobi securities exchange (NSE) is not significant, while Abdulrehman and Nyamute (2018) found a significant relationship between mortgage financing and financial performance of commercial banks in Kenya. Carballo-Huerta and González-Ibarra ( 2008) found positive impact of innovative loans on the expansion of mortgage portfolios and profitability, whereas Gopalakrishnan (2000) and Sarkisyan et al (2009) found no impact. Government owned banks were found to generate a lower volume of NPL and are more profitable in Indonesia (Atahau, 2014), contrary to the evidence in other markets (Iannotta et al, 2007).…”
Section: Introductionmentioning
confidence: 99%